Control Design of Wind Turbine System Using Fuzzy Logic Controller for Middle Voltage Grid - Soedibyo Soedibyo; Feby Agung Pamuji; Mochamad Ashari (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
This paper presents a  system wind turbine in order to have continously electricity supply for 20 kV grid. Output wind turbine controlled by dc-dc boost converter to produce maximum power in order to obtain the MPP (Maximum Power Point). Output of the converter is controlled by fuzzy logic to obtain the MPP (Maximum Power Point) wind turbine, thus the efficiency  wind turbine can be increased. The system of wind turbine is connected to 20 kV grid. From the simulation using matlab 2010 can be conclude that the controller can shift power to 75 % maximum power of wind turbine. DOI: http://dx.doi.org/10.11591/telkomnika.v13i3.7167